2023
DOI: 10.1007/s00330-023-09482-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic tumour and nodal response to neoadjuvant chemotherapy on FDG PET-CT as a predictor of pathological response and survival in patients with oesophageal adenocarcinoma

Abstract: Objectives 2-deoxy-2[18F]Fluoro-d-glucose (FDG) PET-CT has an emerging role in assessing response to neoadjuvant therapy in oesophageal cancer. This study evaluated FDG PET-CT in predicting pathological tumour response (pTR), pathological nodal response (pNR) and survival. Methods Cohort study of 75 patients with oesophageal or oesophago-gastric junction (GOJ) adenocarcinoma treated with neoadjuvant chemotherapy then surgery at Guy’s and St Thomas’ NHS Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Taking homogenous metrics for meta‐analysis left two studies examining SUV max as a positive predictor of OS and PFS. While underpowered, this meta‐analysis serves to highlight the potential future use of SUV max for patient prognostic use, which also appears to have a predictive role in other disease processes 31,32 . Of note, some studies reported differing interpretations of the same metric, for example, Cardenas reported a HR considering a reduction in SUV max greater or less than 62.3%, 28 while Duimering et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Taking homogenous metrics for meta‐analysis left two studies examining SUV max as a positive predictor of OS and PFS. While underpowered, this meta‐analysis serves to highlight the potential future use of SUV max for patient prognostic use, which also appears to have a predictive role in other disease processes 31,32 . Of note, some studies reported differing interpretations of the same metric, for example, Cardenas reported a HR considering a reduction in SUV max greater or less than 62.3%, 28 while Duimering et al .…”
Section: Discussionmentioning
confidence: 98%
“…While underpowered, this meta-analysis serves to highlight the potential future use of SUV max for patient prognostic use, which also appears to have a predictive role in other disease processes. 31,32 Of note, some studies reported differing interpretations of the same metric, for example, Cardenas reported a HR considering a reduction in SUV max greater or less than 62.3%, 28 while Duimering et al reported HRs relating to an MTV greater or less than 35cm 3 . 27 Further study to standardise values to enable consistent reporting which would better allow for inter-study comparison may be prudent.…”
Section: Discussionmentioning
confidence: 99%
“…Active therapeutic monitoring has a pivotal role in NAC for gastric cancer, with the primary goals being assessment of tumor responsiveness to chemotherapy, determining the appropriate course of chemotherapy, and determining the optimal timing of surgery. Previous studies on PET/CT-based response assessments associated with early metabolic changes in esophagogastric junction cancer have shown significant but inconclusive results and have had an emerging role in the response to neoadjuvant treatments [ 14 , 15 ]. In the present study, we assessed patients with locally progressive gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Active therapeutic monitoring has a pivotal role in NAC for gastric cancer, with the primary goals being assessment of tumor responsiveness to chemotherapy, determining the appropriate course of chemotherapy, and determining the optimal timing of surgery. Previous studies on PET/CT-based response assessments associated with early metabolic changes in esophagogastric junction cancer have shown signi cant but inconclusive results and have had an emerging role in the response to neoadjuvant treatments [14,15] . In the present study, we assessed patients with locally progressive gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%